Plants used for hair growth promotion: A review - Rathi, Vaishali; Rathi, Jagdish Chandra; Tamizharasi, S.; Kumar Pathak, Anupam (Pharmacognosy Reviews)
Hair loss is a common and ever increasing problem in cosmetics as well as primary health care practice. It is a universal problem, having affected both sexes of all races to different extents for as long as mankind has existed. Herbal cosmetics are now emerged as the appropriate solution to the current problem, natural product are fancy in cosmetics and about 1000 kinds of plant extract have been examined with respect to hair growth and still it is a fast growing segment with a vast scope of manifold expansion in coming years. This review describe the use of some natural products for hair growth promotion, with a brief description of the major use, plant parts used, the active responsible for effect and the benefit of such product.
Keywords: Hair care; Natural; Herbal formulation; Medicinal plant; Alopecia